Ionizing Radiation Upregulates Glutamine Metabolism and Induces Cell Death via Accumulation of Reactive Oxygen Species. (30th December 2021) - Yang, Pengfei; Luo, Xiangxia; Li, Jin; Zhang, Tianyi; Gao, Xiaoling; Hua, Junrui; Li, Yonghong; Ding, Nan; He, Jinpeng; Zhang, Yanan; Wei, Wenjun; Wang, Jufang; et al.
Abstract : Glutamine metabolism provides energy to tumor cells and also produces reactive oxygen species (ROS). Excessive accumulation of ROS can damage mitochondria and eventually lead to cell death. xCT (SLC7A11) is responsible for the synthesis of glutathione in order to neutralize ROS. In addition, mitophagy can remove damaged mitochondria to keep the cell alive. Ionizing radiation kills tumor cells by causing the accumulation of ROS, which subsequently induces nuclear DNA damage. With this in mind, we explored the mechanism of intracellular ROS accumulation induced by ionizing radiation and hypothesized new methods to enhance the effect of radiotherapy. We used MCF-7 breast cancer cells and HCT116 colorectal cancer cells in our study. The above-mentioned cells were irradiated with different doses of X-rays or carbon ions. Clone formation assays were used to detect cell proliferation, enzyme-linked immunosorbent assay (ELISA) detected ATP, and glutathione (GSH) production, while the expression of proteins was detected by Western blot and quantitative real-time PCR analysis. The production of ROS was detected by flow cytometry, and immunofluorescence was used to track mitophagy-related processes. Finally, BALB/C tumor-bearing nude mice were irradiated with X-rays in order to further explore the protein expression found in tumors with the use of immunohistochemistry. Ionizing radiation increased the protein expressions of ASCT2, GLS, and GLUD in order to upregulate the glutamine metabolic flux in tumor cells. This caused an increase in ATP secretion. Meanwhile, ionizing radiation inhibited the expression of the xCT (SLC7A11) protein and reduced the generation of glutathione, leading to excessive accumulation of intracellular ROS. The mitophagy inhibitor, or knockdown Parkin gene, is able to enhance the ionizing radiation-induced ROS production and increase nucleus DNA damage. This combined treatment can significantly improve the killing effect of radiation on tumor cells. We concluded that ionizing radiation could upregulate the glutamine metabolic flux and enhance ROS accumulation in mitochondria. Ionizing radiation also decreased the SLC7A11 expression, resulting in reduced GSH generation. Therefore, inhibition of mitophagy can increase ionizing radiation-induced cell death.